2021
DOI: 10.3389/fmars.2021.647394
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between Nanoplastics and the Immune System of the Mediterranean Sea Urchin Paracentrotus lividus

Abstract: The present study highlights for the first time the interplay between model nanoplastics, such as the carboxyl-modified polystyrene nanoparticles (PS-COOH, 60 nm) NPs and the coelomocytes of the sea urchin Paracentrotus lividus, a benthic grazer widely distributed in Mediterranean coastal area, upon acute in vitro exposure (4 h) (5 and 25 μg mL–1). Insight into PS-COOH trafficking (uptake and clearance) and effects on immune cell functions (i.e., cell viability, lysosomal membrane stability, and phagocytosis) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 93 publications
2
10
0
1
Order By: Relevance
“…Similar findings have been already reported in our previous study upon exposure to only virgin micro-PS regardless of their size, 29 while no changes in coelomocyte sub-populations including red versus white amoebocytes were observed by short-term in vitro exposure of coelomocytes to PS nanoparticles (60−50 nm). 68 In agreement with previous findings in other biological systems, the increasing trend of ROS over time together with the concomitant decrease of RNS found in coelomocytes of specimens exposed to colonized micro-PS suggested NO scavenging by ROS through the formation of peroxynitrite by reaction between NO and superoxide anions. 69−71 ROS levels increase in larvae, tissues, and immune cells of some marine invertebrate species upon MP exposure.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Similar findings have been already reported in our previous study upon exposure to only virgin micro-PS regardless of their size, 29 while no changes in coelomocyte sub-populations including red versus white amoebocytes were observed by short-term in vitro exposure of coelomocytes to PS nanoparticles (60−50 nm). 68 In agreement with previous findings in other biological systems, the increasing trend of ROS over time together with the concomitant decrease of RNS found in coelomocytes of specimens exposed to colonized micro-PS suggested NO scavenging by ROS through the formation of peroxynitrite by reaction between NO and superoxide anions. 69−71 ROS levels increase in larvae, tissues, and immune cells of some marine invertebrate species upon MP exposure.…”
Section: Resultssupporting
confidence: 92%
“…Therefore, the presence of bacteria on the surface of colonized micro-PS could have stimulated such immunological responses with an increased production of the red pigment. Similar findings have been already reported in our previous study upon exposure to only virgin micro-PS regardless of their size, while no changes in coelomocyte sub-populations including red versus white amoebocytes were observed by short-term in vitro exposure of coelomocytes to PS nanoparticles (60–50 nm) …”
Section: Resultssupporting
confidence: 92%
“…Li et al, 2020;Ling Liu et al, 2021;Liu et al, 2016Liu et al, , 2020Liu et al, , 2019Liuqingqing Liu et al, 2021;Magrì et al, 2018;Manfra et al, 2017;Y. Mao et al, 2020;Mekaru, 2020;Mishra et al, 2019;Murano et al, 2021 Okshevsky et al, 2020;Oriekhova and Stoll, 2018;Pradel et al, 2021;Ramirez Arenas et al, 2020;Ramirez et al, 2019;Reynolds et al, 2019;Ripken et al, 2020;Rowenczyk et al, 2021;Saavedra et al, 2019;Schampera et al, 2021;Sendra et al, 2020Sendra et al, , 2019Seoane et al, 2019;Shiu et al, 2020aShiu et al, , 2020bShupe et al, 2021;Silva et al, 2020;Singh et al, 2021Singh et al, , 2019Song et al, 2019;Summers et al, 2018;Tallec et al, 2019;Trevisan et al, 2019;Vaz et al, 2021;Venel et al, 2021;Wang et al, 2021Wang et al, , 2020Wegner et al, 2012;Wu et al, 2021Wu et al, , 2019…”
Section: Methodsunclassified
“…Using the same model organism, Kelpsiene et al reported a reduced life-time upon exposure to polystyrene nanoplastics [ 20 ]. Of note, some studies reported translocation in a surface charge-dependent manner in both marine organisms and rats [ 8 , 21 ]. Based on these observations and the fact that due to weathering processes and subsequent surface oxidation, microplastic particles are expected to acquire carboxylic groups (-COOH) and hence are negatively charged [ 22 ], we therefore have used carboxylated PS particles in our study as well.…”
Section: Discussionmentioning
confidence: 99%